Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka Belajar pada Mata Pelajaran Pendidikan Agama Kristen di SMP Negeri 5 Mamasa - Semuel (PEADA': Jurnal Pendidikan Kristen, 2024)
The independent learning curriculum is the government's effort to advance education in Indonesia. One of the approaches in order to realize independent learning is the differentiated learning approach. Differentiated learning is one of the approaches that can be implemented by teachers to meet the needs of students according to their readiness, interests and learning profiles. However, differentiated learning is still rarely done due to teachers' lack of understanding in designing learning. This is because this curriculum is a newly implemented curriculum and not all education units have fully implemented it. The purpose of this study is to assist teachers in implementing learning in the classroom based on needs and applying differentiated learning strategies, namely content, process, and product so that together they can achieve educational goals. The research was conducted at SMPN 5 Mamasa from Mei to Juli 2023 using qualitative research methods with a descriptive analysis approach. The participants in this research are teachers and students. The focus of the research is to explain the stages of differentiated learning in Christian Religious Education subjects with the material of the Bible as the guide of my life. The results of this study show that differentiated learning has a positive impact on students and can help teachers to be able to fulfil their duties and responsibilities through the stages of preparing initial mapping with diagnostic assessments, compiling learning modules, and implementing learning.